Prime editing in plants and mammalian cells: Mechanism, achievements, limitations, and future prospects - Hillary, V. Edwin; Ceasar, S. Antony (BioEssays, 2022)
Clustered, regularly interspaced, short palindromic repeat (CRISPR)/CRISPR‐associated protein (CRISPR/Cas) system has revolutionized genetic research in the life sciences. Four classes of CRISPR/Cas‐derived genome editing agents, such as nuclease, base editor, recombinase, and prime editor have been introduced for engineering the genomes of diverse organisms. The recently introduced prime editing system offers precise editing without many off‐target effects than traditional CRISPR‐based systems. Many researchers have successfully applied this gene‐editing toolbox in diverse systems for various genome‐editing applications. This review presents the mechanism of prime editing and summarizes the details of the prime editing system applied in plants and mammalian cells for precise genome editing. We also discuss the advantages, limitations, and potential future applications of prime editing in these systems. This review enables the researcher to gain knowledge on prime editing tools and their potential applications in plants and mammalian cells. Prime editing is a search‐and‐replace genome editing system, which mediates all possible 12 base‐to‐base conversions without DSBs and donor templates at a targeted sequence. We describe how this prime editing system helps in improving genetic studies in plants and mammalian cells with their mechanism, achievements, limitations, and future prospects.